Perigo, probabilidade e oportunidade: a linguagem dos riscos na mídia - SPINK, Mary Jane Paris (2016)
Based on the assumption that risk is a central concept in contemporary society, the study aims to understand the role of the media in the circulation and consolidation of the language of risks. The Folha de S. Paulo, a major Brazilian newspaper, was used as a source of data. Research procedures involved: 1) mapping the diversity of terms used for talking about the possibility of occurrence of events seen as occasions for loss or gain; 2) diachronic analysis of a representative sample of news-items with the word risk on the title (1921-1998); 3) analysis of the use of the language of risks by subject area (CD-Rom Folha, 1994-1997). The results suggest that the use of the language of risks in the media is recent and diversified with emphasis on both, the formal language of risk calculations and its metaphoric use for talking about disorder in contemporary society.